The feasibility study of extradural nerve anastomosis technique for canine bladder reinnervation after spinal cord injury. (1st November 2016) - Tang, Jian; Ma, Jun; Yang, Lei; Huang, Xinpeng; Ge, Yingbin; Sui, Tao; Wei, Zhongqing; Cao, Xiaojian
Abstract : Objective : Intradural nerve anastomosis for bladder innervation has been demonstrated to be useful. However, its clinical application remains limited because of the complex surgery, its complications and extensive bony destruction. The purpose of the current study was to demonstrate the feasibility of extradural spinal root anastomosis for bladder innervation in canines. Methods : Ten beagle dogs were used. The length of the extradural segment of the nerve root, upper nerve root outlet (the point at which it emerges from the spinal dura mater) to S2 (dS2), the S3 (dS3) nerve root outlet distance, and the diameters of the extradural spinal roots were measured. The numbers of nerve fibers from L6 to S3 ventral roots were calculated using immunohistochemical staining. Results : The extradural spinal roots could be divided into a ventral root (VR) and a dorsal root (DR) before the ganglionic enlargement of the dorsal root, and the extradural motor nerve roots situate ventrally to their corresponding sensory nerve roots. The extradural nerve root lengths of S1 and parts of L7 were longer than the corresponding dS2. The numbers of nerve and motor nerve fibers, and the diameters of extradural nerve roots, were gradually descending from L6 to S3. Conclusion : The S1 VRs and parts of the L7 VRs can be extradurally anastomosed to the S2 nerves without tension. A nerve graft was needed for extradural anastomosis of L6 VRs and parts of L7 VRs to S2 VRs. This study demonstrated the feasibility of extradural spinal nerve anastomosis for treating neurogenic bladder in canines.